The Effect of Climate Change on the Spread of Communicable Diseases in Urban Environments - Anita Lontaan; Esa Zahirah; Yayuk Sri Rahayu; Radeny Ramdany (Miracle Journal Get Press, 2024)
Climate change is one of the biggest global challenges of the 21st century with far-reaching impacts on various sectors, including public health. This research aims to study how climate change affects the spread of infectious diseases in urban environments, with an emphasis on environmental and behavioural factors that influence the spread of disease. The quantitative method used in this study is descriptive-analytic design. Descriptive research is used to describe the phenomenon of the spread of infectious diseases in urban environments associated with climate change components such as air temperature, rainfall, and humidity. Over five years, the incidence rate of dengue fever in West Sumatra has fluctuated and continued to increase. As shown, the rainfall pattern is changing and increasing. The picture shows a trend of increasing rainfall along with an increase in the number of dengue cases. However, there is a time difference, or time lag, between the increase in cases. Every region should have an early warning system for extraordinary dengue events. As climatic factors change, environmental improvements are also needed along with changes in other factors such as behaviour and health services.